Rancang Bangun Aplikasi Presensi Karyawan Berbasis Web untuk Meningkatkan Efisiensi di PT Nyonya Lin Jaya - Arditya Ihza Pramana Putera; Farizi Ilham; Abiyu Rafi Khambali; Dzifqi Akbar Amrulloh (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The rapid advancement of information technology encourages companies to adopt digital systems to improve operational efficiency, including employee attendance management. PT Nyonya Lin Jaya, a Mixue franchise partner, still uses a manual attendance system that causes several problems, such as slow attendance recapitulation, recording errors, and potential attendance fraud. This study aims to design and develop a web based employee attendance application capable of managing attendance data automatically and accurately. The system development method used is the Waterfall model, which consists of requirements analysis, system design, implementation, and testing stages. The system was developed using PHP, Laravel Framework, MySQL, and geolocation technology to validate employee locations during attendance recording. The results indicate that the developed system simplifies attendance recording, provides real-time attendance monitoring, and automatically generates attendance reports. The implementation of this system is expected to improve administrative efficiency and support management decision-making related to human resource management at PT Nyonya Lin Jaya.